Book Excerpt: Islamic fund and wealth management: a way forward - Haron, Razali; Abdullah, Adam (REDmoney Group, 2019)
This book specifically provides updated information on fund and wealth management with regards to current policies and best practices. Empirical findings, case studies discussions, seminal as well as recent related literature are gathered in this book to cater to everyone inside or outside the fund and wealth management industry.